Why English is fundamental in an increasingly interconnected world - McCarthy, N. (Acta Biomedica Atenei Parmensis, 2007)
In the last few years, the advances in technological progress have been amazing. Given the importance of English as the main means of communication in our increasingly interconnected world, it is a pity that schools, and to a lesser degree universities, do not put more emphasis on the acquisition of listening and speaking skills since, when it comes to speaking English, Italian students do not fare brilliantly compared to those in the rest of Europe. Of the 4 medical schools viewed in Italy, Parma gives the least importance to learning Medical English.When comparing universities in Europe, the French come out on top, putting a lot of emphasis on learning Medical English.